Forgotten masters Pieter Pourbus and Bruges painting from 1525 to 1625 - Oosterwijk, Anne van; Bassens, Maarten (Snoeck, 2017)
Unknown, unloved: this certainly applies to the Bruges-based masters from the sixteenth century. Ambrosius Benson, Lancelot Blondeel, Pieter Pourbus and the Claeissens family are in the shadow of their predecessors, the Flemish primitives, and their contemporaries from Antwerp. Bruges' golden age is over and the market has changed. Inspired by its glorious artistic past, a totally new style arises in Bruges. This book focuses on these forgotten masters. Exhibition: Groeningemuseum, Bruges, Belgium (13.10.2017-21.01.2018)
Titel der Ausstellung: Pieter Pourbus and the forgotten masters
Keywords: Claeissens, Pieter -- 1536-1623; Isenbrant, Adriaen -- 1490-1551; Claeissens -- Familie -- ca. 16. Jh.; Benson, Ambrosius -- 1495-1550; Claeissens, Gillis -- 1536-1605; Pourbus, Pieter Jansz -- 1523-1584; Pourbus, Frans -- 1569-1622; Claeissens, Pieter -- 1499-1576; Blondeel, Lancelot -- 1498-1561; Claeissens, Antoon -- 1536-1613; Pourbus, Frans -- 1545-1581; Gheeraerts, Marcus -- 1520-1590; Geschichte 1525-1625; Malerei; Flandern; Brügge; Pourbus, Pieter Jansz. / 1523 or 1524-1584 / Exhibitions; Painting, Belgian / 16th century / Exhibitions; Painters / Belgium / Bruges / 16th century / Exhibitions; Painting / Belgium / Bruges / History / 16th century / Exhibitions; Ausstellungskatalog -- Groeningemuseum -- 13.10.2017-21.01.2018 -- Brügge